2021
DOI: 10.1111/jocs.15372
|View full text |Cite
|
Sign up to set email alerts
|

Toward stroke‐free coronary surgery: The role of the anaortic off‐pump bypass technique

Abstract: Surgical coronary revascularization remains the preferred strategy in a significant portion of patients with coronary artery disease due to superior long‐term outcomes. However, there is a significant risk of perioperative neurologic injury that has influenced guideline recommendations. These complications occur in 1%–5% of patients, ranging from overt neurologic deficits with permanent disability, to subtle cerebral defects noted on neuroimaging that may result in slow cognitive and functional decline. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 84 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…The main cause of perioperative stroke remains emboli, and the main source of emboli stems from the aortic manipulation associated with cannulation, "sandblasting" from the aortic cannula inflow jet, crossclamping, and proximal anastomoses that are inherent to the on-pump, arrested heart CABG technique. 17 Perioperative and delayed stroke have been shown to have a highly significant impact on mortality, with a meta-regression analysis showing that minimizing aortic manipulation, rather than intrinsic patient characteristics, had a protective effect on neurologic outcomes. 18 A network meta-analysis performed by our group in 2017 identified that stepwise reduction and ultimately elimination of aortic manipulation resulted in superior neurologic outcome (and also superior early mortality, renal failure, bleeding, atrial fibrillation, and shorter length of intensive care) (Figure 1).…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause of perioperative stroke remains emboli, and the main source of emboli stems from the aortic manipulation associated with cannulation, "sandblasting" from the aortic cannula inflow jet, crossclamping, and proximal anastomoses that are inherent to the on-pump, arrested heart CABG technique. 17 Perioperative and delayed stroke have been shown to have a highly significant impact on mortality, with a meta-regression analysis showing that minimizing aortic manipulation, rather than intrinsic patient characteristics, had a protective effect on neurologic outcomes. 18 A network meta-analysis performed by our group in 2017 identified that stepwise reduction and ultimately elimination of aortic manipulation resulted in superior neurologic outcome (and also superior early mortality, renal failure, bleeding, atrial fibrillation, and shorter length of intensive care) (Figure 1).…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
“…The main cause of perioperative stroke remains emboli, and the main source of emboli stems from the aortic manipulation associated with cannulation, “sandblasting” from the aortic cannula inflow jet, crossclamping, and proximal anastomoses that are inherent to the on-pump, arrested heart CABG technique. 17 Perioperative and delayed stroke have been shown to have a highly significant impact on mortality, with a meta-regression analysis showing that minimizing aortic manipulation, rather than intrinsic patient characteristics, had a protective effect on neurologic outcomes. 18 …”
Section: Whymentioning
confidence: 99%
“…Operative mortality is increased 12-fold in patients with stroke. 8,9 Off-pump and anaortic techniques reduce embolization in patients undergoing CABG and may protect against stroke. 9 What is clear is that embolization is the underlying mechanism of stroke in a significant proportion of cardiac surgical patients.…”
mentioning
confidence: 99%
“…Stroke rates of ~1% are noted after cardiac surgery but may be much higher depending on the procedure and patient characteristics, especially severe aortic atherosclerosis. Operative mortality is increased 12‐fold in patients with stroke 8,9 . Off‐pump and anaortic techniques reduce embolization in patients undergoing CABG and may protect against stroke 9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation